High-strength corrugated paper and preparation method thereof
By adding denatured starch, epoxy resin, phenolic resin and modified nanomaterial to the reinforcement liquid of corrugated paper, the problem of adhesive failure of corrugated paper at high temperature is solved, and the high strength and high temperature stability of corrugated paper is achieved.
Patent Information
- Application Number
- CN202510264715.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-05-02
AI Technical Summary
The adhesive of existing corrugated paper softens or fails at high temperatures, resulting in the delamination or strength of the cardboard, which cannot meet the needs of use in high temperature environments.
By adding denatured starch, epoxy resin, phenolic resin and modified nanomaterial to the reinforcement liquid of corrugated paper, a complex mesh structure is formed to enhance the compressive strength of corrugated paper and the bonding strength at high temperatures.
It significantly improves the compressive strength of corrugated paper and the bonding strength at high temperatures, ensuring that the cardboard remains intact and strong under high temperature environments.
Smart Images

Figure BDA0005301240220000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrugated paper, and particularly relates to high-strength corrugated paper and a preparation method thereof. Background Art
[0002] Corrugated paper is a kind of paperboard made of one or several layers of corrugated paperboard (called corrugated core paper) bonded with flat paper, which has good cushioning, shock absorption and protection properties. It is widely used in the packaging industry, especially in making cartons, packaging boxes, etc.
[0003] The main function of corrugated paper is to package and protect the internal items. High-strength corrugated paper can better resist external pressure, thereby reducing damage to the contents, especially in the case of frequent logistics turnover, extending the service life of the carton. At the same time, in some special use environments, some products need to be stored or transported in a high temperature environment. For example, in hot areas, the temperature in the transport vehicle will exceed 50°C, and the corrugated box needs to remain intact under such conditions. Some medical supplies or food packaging may need to be sterilized at high temperatures, and the packaging materials must be resistant to high temperatures; the aircraft cargo hold may experience a large temperature difference during takeoff and landing, and the temperature in some areas may reach above 50°C. However, the adhesive of corrugated paper in the prior art may soften or even fail at high temperatures, resulting in delamination or loss of strength of the cardboard. At the same time, high temperatures may cause the cardboard fibers to soften, causing the cardboard to lose its original rigidity and shape.
[0004] The surface sizing agent model GBS-02 of Guangzhou Tongda Chemical Engineering Co., Ltd. is a water-based multi-polymer emulsion made by a specific process. It is suitable for use as a surface sizing agent in the papermaking industry, especially for packaging paper (such as high-strength corrugated paper and kraft linerboard). The emulsion is very easy to spread and bind on the fiber surface. It has a variety of active functional groups in its molecular structure, which can give the paper a number of excellent properties, such as improving the paper's water resistance and ring crush strength. This product is widely used by manufacturers of corrugated paper, but in practice it is found that the bonding strength of corrugated paper prepared using the above surface sizing agent at high temperatures is not ideal.
[0005] Chinese patent CN202311003100.5 discloses a new type of high-strength corrugated paperboard and its processing technology. Through unique cross-linking hardening liquid treatment, the bonding force is greatly improved, thereby improving the overall strength of the corrugated paperboard, and having good bonding strength at 50°C. However, this product still cannot meet the needs of consumers who have higher temperature requirements for use conditions.
[0006] Therefore, there is an urgent need for a high-strength corrugated paper and a preparation method thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a high-strength corrugated paper and a preparation method thereof.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A high-strength corrugated paper, comprising, from outside to inside, a face paper, a corrugated paperboard layer and an inner paper layer, wherein the corrugated paperboard layer is obtained by soaking the corrugated paperboard in a reinforcing liquid and then drying it, and the corrugated paperboard layer is adhered to the surface of the face paper and the inner paper layer respectively by an adhesive;
[0010] The enhancement liquid comprises the following raw materials in parts by weight: 18-22 parts of modified starch, 4-6 parts of epoxy resin, 1-3 parts of phenolic resin, 0.5-1 parts of dicyandiamide, 0.1-0.2 parts of dibutyltin dilaurate, 5-7 parts of modified nanomaterials, 2-5 parts of organosilicon modifiers, 0.1-0.2 parts of epichlorohydrin, 80-90 parts of acetone and 30-40 parts of water.
[0011] Furthermore, the preparation method of the modified starch comprises the following steps: by weight, 1 part of starch, 0.3-0.4 parts of sodium hydroxide, 0.02-0.05 parts of urea, and 0.2-0.4 parts of 80-85 (v / v)% ethanol aqueous solution are mixed and reacted; 0.1-0.2 parts of disodium hydrogen phosphate are added to continue the reaction; 0.2-0.5 parts of monochloroacetic acid are added to react to obtain modified starch.
[0012] Furthermore, the preparation method of the modified starch comprises the following steps: by weight, 1 part of starch, 0.3-0.4 parts of sodium hydroxide, 0.02-0.05 parts of urea, and 0.2-0.4 parts of 80-85 (v / v)% ethanol aqueous solution are mixed, and the mixture is reacted at 25-30° C. for 30-40 minutes; 0.1-0.2 parts of disodium hydrogen phosphate are continuously added, and the mixture is reacted at 35° C.-40° C. for 70-90 minutes; the mixture is heated to 80-85° C., 0.2-0.5 parts of monochloroacetic acid are added, and the mixture is heated and reacted for 70-90 minutes to obtain the modified starch.
[0013] The present invention can improve the compressive strength and the bonding strength of corrugated paper at room temperature by adding epoxy resin and phenolic resin to modified starch. The present invention sequentially performs esterification and etherification treatment on starch to obtain modified starch, and then adds epoxy resin and phenolic resin. The modified starch, epoxy resin and phenolic resin synergistically form a complex network structure to enhance the compressive strength of the corrugated paper. At the same time, since the components in the reinforcing liquid have modified the corrugated paperboard in advance, the surface sizing agent is more likely to penetrate into between paper fibers and can interact with the previously formed resin network, thereby improving the bonding strength.
[0014] Furthermore, the modified nanomaterial is prepared by mixing titanium dioxide, silicon carbide and boron nitride, adding water and hexadecyltrimethylammonium bromide, and heating for reaction.
[0015] Furthermore, the weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:(1.2-1.4):(0.5-0.7).
[0016] Furthermore, the titanium dioxide has a particle size of 10-20 nm and a specific surface area of 30-100 m 2 / g. The particle size of silicon carbide is 20-60nm, and the specific surface area is 20-30m 2 / g. The particle size of boron nitride is 80-140nm, and the specific surface area is 10-20m 2 / g.
[0017] Furthermore, the preparation method of the modified nanomaterial comprises the following steps:
[0018] (1) mixing titanium dioxide, silicon carbide and boron nitride to obtain a mixed material;
[0019] (2) mixing the mixed material and water, adjusting the pH, and stirring to form a suspension;
[0020] (3) adding hexadecyltrimethylammonium bromide to the suspension, mixing, stirring for reaction, filtering, washing, and drying to obtain a modified nanomaterial.
[0021] Furthermore, the preparation method of the modified nanomaterial comprises the following steps:
[0022] (1) mixing titanium dioxide, silicon carbide and boron nitride to obtain a mixed material;
[0023] (2) mixing the mixed material and water in a weight ratio of 1:(6-8), adjusting the pH value to 9.5-10 using sodium carbonate, and stirring at 60-65° C. for 3-5 hours to form a suspension;
[0024] (3) Add hexadecyltrimethylammonium bromide to the suspension, mix and stir evenly, react at 60-65° C. for 4-6 hours, filter, wash to neutrality, and dry to obtain a modified nanomaterial.
[0025] The present invention can improve the compressive strength of corrugated paper and the bonding strength of corrugated paper at high temperature by adding modified nano materials to the reinforcing liquid. When the modified nano materials are introduced into the reinforcing liquid of the corrugated paper, they can be evenly dispersed to form a "bridging" effect, strengthen the bonding force between the components, and thus improve the overall compressive strength of the corrugated paper. At the same time, there is a complex synergistic effect between the modified nano materials and other reinforcing liquid components, forming a more compact composite system, forming a multi-phase collaborative reinforcing network, and realizing the simultaneous improvement of the high-temperature bonding strength of the corrugated paper.
[0026] Furthermore, the amount of cetyltrimethylammonium bromide added is 10-15% by weight of the mixed material.
[0027] Furthermore, the organosilicon modifier is KH-570 silane coupling agent.
[0028] Furthermore, the preparation method of the enhancement solution comprises the following steps:
[0029] (1) mixing modified starch, phenolic resin, modified nanomaterial and water, heating and stirring at 60-70° C. for 45-50 minutes, and cooling to room temperature to obtain an aqueous phase system;
[0030] (2) mixing epoxy resin, dicyandiamide, dibutyltin dilaurate, organosilicon modifier, aminosilicone oil, epichlorohydrin and acetone, stirring at 50-60° C. for 40-50 min, and cooling to room temperature to obtain an acetone phase system;
[0031] (3) The aqueous phase system is added to the acetone phase system, and stirred at a rotation speed of 1200-1500 rpm and 50-60° C. for 30-50 min to obtain an enhanced solution.
[0032] The present invention also provides a method for preparing high-strength corrugated paper, comprising the following steps:
[0033] (1) applying a reinforcing liquid to the surface of a corrugated paper layer and drying the layer to obtain a corrugated paper layer;
[0034] (2) The rigid corrugated paper layer is adhered to the surface of the face paper and the inner paper by an adhesive to obtain a high-strength new type of corrugated paperboard.
[0035] The present invention also provides a method for preparing high-strength corrugated paper, comprising the following steps:
[0036] (1) applying a reinforcing liquid to the surface of the corrugated paper layer, drying at 50-55° C. for 25-30 hours, wherein the reinforcing layer obtained after the reinforcing liquid is dried has a thickness of 2-4 μm, and a corrugated paper layer is obtained;
[0037] (2) The rigid corrugated paper layer is adhered to the surface of the face paper and the inner paper by an adhesive, wherein the adhesive is a surface sizing agent of model GBS-02, to obtain a high-strength new type of corrugated paperboard.
[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0039] 1. The present invention can improve the compressive strength and bonding strength of corrugated paper at room temperature by adding epoxy resin and phenolic resin to modified starch.
[0040] 2. The present invention can improve the compressive strength of corrugated paper and the bonding strength of corrugated paper at high temperature by adding modified nanomaterials into the reinforcing liquid. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The raw materials used in the following examples of the present invention are all commercially available products:
[0043] Adhesive: Guangzhou Tongda Chemical Engineering Co., Ltd., surface sizing agent, model GBS-02.
[0044] Corrugated cardboard, Shijiazhuang Shengrunxuan Paper Products Co., Ltd., single-sided corrugated cardboard, thickness 2mm.
[0045] Epoxy resin, Shandong Pinshang New Materials Co., Ltd., Phoenix brand WSR 6101 epoxy resin.
[0046] Phenolic resin, Shanghai MacLean Biochemical Technology Co., Ltd., product number P875865.
[0047] Example 1
[0048] This embodiment provides a high-strength corrugated paper, which includes, from outside to inside, a face paper, a corrugated paperboard layer and an inner paper layer, wherein the corrugated paperboard layer is obtained by soaking the corrugated paperboard in a reinforcing liquid and then drying it, and the corrugated paperboard layer is adhered to the surface of the face paper and the inner paper layer respectively by an adhesive;
[0049] The reinforcing liquid comprises the following raw materials in parts by weight: 20 parts of modified starch, 5 parts of epoxy resin, 2 parts of phenolic resin, 0.7 parts of dicyandiamide, 0.15 parts of dibutyltin dilaurate, 6 parts of modified nanomaterials, 3 parts of organosilicon modifier, 0.16 parts of epichlorohydrin, 85 parts of acetone and 35 parts of water. The organosilicon modifier is KH-570 silane coupling agent.
[0050] The preparation method of the modified starch comprises the following steps: by weight, 1 part of starch, 0.35 parts of sodium hydroxide, 0.04 parts of urea, and 0.3 parts of 82 (v / v)% ethanol aqueous solution are mixed, and the mixture is reacted at 27° C. for 35 minutes; 0.15 parts of disodium hydrogen phosphate are added, and the mixture is reacted at 37° C. for 80 minutes; the temperature is further raised to 82° C., 0.4 parts of monochloroacetic acid are added, and the mixture is kept warm for reaction for 80 minutes to obtain the modified starch.
[0051] The preparation method of the modified nanomaterial comprises the following steps:
[0052] (1) Titanium dioxide, silicon carbide and boron nitride are mixed to obtain a mixed material; the weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:1.3:0.6. The particle size of the titanium dioxide is 10-20 nm, and the specific surface area is 30-100 m 2 / g; Beijing Dekedaojin Technology Co., Ltd. The particle size of silicon carbide is 20-60nm, and the specific surface area is 20-30m 2 / g; Chengdu Jiacai Technology Co., Ltd. The particle size of boron nitride is 80-140nm, and the specific surface area is 10-20m 2 / g; Zhejiang Zhiti Nano New Materials Co., Ltd.
[0053] (2) mixing the mixed material and water in a weight ratio of 1:7, adjusting the pH value to 9.7 using sodium carbonate, and stirring at 62° C. for 4 h to form a suspension;
[0054] (3) adding hexadecyltrimethylammonium bromide to the suspension and mixing, wherein the amount of hexadecyltrimethylammonium bromide added is 12% by weight of the mixed material; stirring evenly, reacting at 62° C. for 5 h, filtering, washing to neutrality, and drying to obtain a modified nanomaterial.
[0055] The preparation method of the enhancement solution comprises the following steps:
[0056] (1) mixing modified starch, phenolic resin, modified nanomaterials and water, heating and stirring at 65° C. for 47 minutes, and cooling to room temperature to obtain an aqueous phase system;
[0057] (2) mixing epoxy resin, dicyandiamide, dibutyltin dilaurate, organosilicon modifier, aminosilicone oil, epichlorohydrin and acetone, stirring at 55° C. for 45 min, and cooling to room temperature to obtain an acetone phase system;
[0058] (3) The aqueous phase system was added to the acetone phase system, and the mixture was stirred at 55° C. for 40 min at a rotation speed of 1300 rpm to obtain an enhanced solution.
[0059] The method for preparing the high-strength corrugated paper comprises the following steps:
[0060] (1) applying a reinforcing liquid to the surface of the corrugated paper layer, and drying at 52° C. for 27 h. After the reinforcing liquid is dried, a reinforcing layer with a thickness of 3 μm is obtained on the surface of the corrugated paper layer, thereby obtaining a corrugated paperboard layer;
[0061] (2) The rigid corrugated paper layer is adhered to the surface of the face paper and the inner paper by an adhesive to obtain a high-strength new type of corrugated paperboard.
[0062] Example 2
[0063] This embodiment provides a high-strength corrugated paper, which includes, from outside to inside, a face paper, a corrugated paperboard layer and an inner paper layer, wherein the corrugated paperboard layer is obtained by soaking the corrugated paperboard in a reinforcing liquid and then drying it, and the corrugated paperboard layer is adhered to the surface of the face paper and the inner paper layer respectively by an adhesive;
[0064] The reinforcing liquid comprises the following raw materials in parts by weight: 22 parts of modified starch, 4 parts of epoxy resin, 3 parts of phenolic resin, 0.5 parts of dicyandiamide, 0.2 parts of dibutyltin dilaurate, 5 parts of modified nanomaterials, 5 parts of organosilicon modifier, 0.2 parts of epichlorohydrin, 80 parts of acetone and 40 parts of water. The organosilicon modifier is KH-570 silane coupling agent.
[0065] The preparation method of the modified starch comprises the following steps: by weight, 1 part of starch, 0.3 parts of sodium hydroxide, 0.05 parts of urea and 0.2 parts of 85 (v / v)% ethanol aqueous solution are mixed, and the mixture is reacted at 25° C. for 40 minutes; 0.1 parts of disodium hydrogen phosphate are added, and the mixture is reacted at 40° C. for 90 minutes; the mixture is heated to 80° C., 0.5 parts of monochloroacetic acid are added, and the mixture is heated and reacted for 70 minutes to obtain the modified starch.
[0066] The preparation method of the modified nanomaterial comprises the following steps:
[0067] (1) Titanium dioxide, silicon carbide and boron nitride are mixed to obtain a mixed material; the weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:1.2:0.7. The particle size of the titanium dioxide is 10-20 nm, and the specific surface area is 30-100 m 2 / g; Beijing Dekedaojin Technology Co., Ltd. The particle size of silicon carbide is 20-60nm, and the specific surface area is 20-30m 2 / g; Chengdu Jiacai Technology Co., Ltd. The particle size of boron nitride is 80-140nm, and the specific surface area is 10-20m 2 / g; Zhejiang Zhiti Nano New Materials Co., Ltd.
[0068] (2) mixing the mixed material and water in a weight ratio of 1:8, adjusting the pH value to 10 using sodium carbonate, and stirring at 60° C. for 5 h to form a suspension;
[0069] (3) adding hexadecyltrimethylammonium bromide to the suspension and mixing, wherein the amount of hexadecyltrimethylammonium bromide added accounts for 10% of the weight percentage of the mixed material; stirring evenly, stirring and reacting at 60° C. for 6 hours, filtering, washing to neutrality, and drying to obtain a modified nanomaterial.
[0070] The preparation method of the enhancement solution comprises the following steps:
[0071] (1) mixing modified starch, phenolic resin, modified nanomaterials and water, heating and stirring at 70° C. for 45 min, and cooling to room temperature to obtain an aqueous phase system;
[0072] (2) mixing epoxy resin, dicyandiamide, dibutyltin dilaurate, organosilicon modifier, aminosilicone oil, epichlorohydrin and acetone, stirring at 60° C. for 40 min, and cooling to room temperature to obtain an acetone phase system;
[0073] (3) The aqueous phase system was added to the acetone phase system, and stirred at 50° C. for 50 min at a rotation speed of 1500 rpm to obtain an enhanced solution.
[0074] The method for preparing the high-strength corrugated paper comprises the following steps:
[0075] (1) applying a reinforcing liquid to the surface of the corrugated paper layer, and drying at 50° C. for 30 h. After the reinforcing liquid is dried, a reinforcing layer with a thickness of 3 μm is obtained on the surface of the corrugated paper layer, thereby obtaining a corrugated paperboard layer;
[0076] (2) The rigid corrugated paper layer is adhered to the surface of the face paper and the inner paper by an adhesive to obtain a high-strength new type of corrugated paperboard.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 1 is that the modified starch is replaced by commercially available modified starch purchased from Huantai County Jinhu Modified Starch Factory.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 1 is that the weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:1:1.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that the particle size of the titanium dioxide is 50-80nm and the specific surface area is 10-20m 2 / g; Beijing Dekedaojin Technology Co., Ltd. The particle size of silicon carbide is 100-150nm, and the specific surface area is 5-10m 2 / g; Chengdu Jiacai Technology Co., Ltd. The particle size of boron nitride is 150-200nm, and the specific surface area is 4-10m 2 / g; Zhejiang Zhiti Nano New Materials Co., Ltd.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 1 is:
[0085] The preparation method of the modified nanomaterial comprises the following steps:
[0086] (1) Titanium dioxide, silicon carbide and boron nitride are mixed to obtain a mixed material; the weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:1.3:0.6. The particle size of the titanium dioxide is 10-20 nm, and the specific surface area is 30-100 m 2 / g; Beijing Dekedaojin Technology Co., Ltd. The particle size of silicon carbide is 20-60nm, and the specific surface area is 20-30m 2 / g; Chengdu Jiacai Technology Co., Ltd. The particle size of boron nitride is 80-140nm, and the specific surface area is 10-20m 2 / g; Zhejiang Zhiti Nano New Materials Co., Ltd.
[0087] (2) The mixed material, acetone and silane coupling agent KH550 in a weight ratio of 1:6:0.1 were mixed, stirred at 40° C. for 5 h, filtered and dried to obtain a modified nanomaterial.
[0088] Comparative Example 5
[0089] This comparative example is prepared according to the method of Example 3 in Chinese patent CN202311003100.5, a new type of high-strength corrugated paperboard and its processing technology.
[0090] Performance Testing
[0091] The performance tests were performed on the corrugated papers prepared in Examples 1-2 and Comparative Examples 1-5.
[0092] (1) Edge compression strength: refer to GB / T 6546-2021 "Determination of edge compression strength of Wabang paperboard".
[0093] (2) Flat compression strength: refer to GB / T 22874-2008 "Determination of flat compression strength of single-faced and single-wall corrugated board".
[0094] (3) Adhesion strength: refer to GB / T 6548-2011 "Determination of adhesion strength of corrugated board"
[0095] (4) Water resistance: refer to GB / T 22873-2008 “Determination of water resistance of adhesives on corrugated board (immersion method)”.
[0096] Table 1 Performance test results
[0097]
[0098] It can be seen from the above performance test results that the corrugated paper of Examples 1-2 has high strength, good high temperature resistance and strong waterproofness.
[0099] In Comparative Example 1, commercially available modified starch was used, and it can be seen that the compressive strength decreased and the adhesive strength at room temperature decreased, which proves that the modified starch prepared by the present invention and the other components in the system can better play a synergistic role and improve the comprehensive performance of corrugated paper.
[0100] The ratios of titanium dioxide, silicon carbide and boron nitride in Comparative Example 2 are different, and the parameters of titanium dioxide, silicon carbide and boron nitride in Comparative Example 3 are different. The results show that the compressive strength and the bonding strength at high temperature of the corrugated paper are affected. This shows that the titanium dioxide, silicon carbide and boron nitride with the specific parameters and ratios of the present invention are suitable for forming a more stable system in the system of the present invention, and can achieve stable bonding with the surface paper under high temperature conditions under the action of the surface sizing agent.
[0101] In Comparative Example 4, titanium dioxide, silicon carbide and boron nitride were modified with silane coupling agent, and the effect was worse than that with hexadecyltrimethylammonium bromide, indicating that the nanomaterial of the present invention has a better dispersion effect in the system after being modified with hexadecyltrimethylammonium bromide.
[0102] In Comparative Example 5, the preparation method in the prior art was used, and the bonding strength at high temperature decreased, indicating that the cross-linked hardening liquid in Comparative Example 5 had poor bonding strength with the surface paper at high temperature under the action of the surface sizing agent of model GBS-02, and was not suitable for corrugated paper prepared with this model of surface sizing agent.
[0103] The above experimental results further prove the importance of the technical solution defined in the present invention to its technical effect.
[0104] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength corrugated paper, characterized in that: The paperboard comprises a face paper, a corrugated paperboard layer and an inner paper layer in order from the outside to the inside. The corrugated paperboard layer is obtained by soaking the corrugated paperboard in a reinforcing liquid and then drying it. The corrugated paperboard layer is respectively adhered to the surface of the face paper and the inner paper layer by an adhesive. The enhancement liquid comprises the following raw materials in parts by weight: 18-22 parts of modified starch, 4-6 parts of epoxy resin, 1-3 parts of phenolic resin, 0.5-1 parts of dicyandiamide, 0.1-0.2 parts of dibutyltin dilaurate, 5-7 parts of modified nanomaterials, 2-5 parts of organosilicon modifiers, 0.1-0.2 parts of epichlorohydrin, 80-90 parts of acetone and 30-40 parts of water.
2. The high-strength corrugated paper according to claim 1, characterized in that: The preparation method of modified starch comprises the following steps: mixing 1 part of starch, 0.3-0.4 parts of sodium hydroxide, 0.02-0.05 parts of urea and 0.2-0.4 parts of ethanol aqueous solution by weight, reacting at 25-30° C. for 30-40 minutes; continuously adding 0.1-0.2 parts of disodium hydrogen phosphate, reacting at 35-40° C. for 70-90 minutes; continuously heating to 80-85° C., adding 0.2-0.5 parts of monochloroacetic acid, and keeping the temperature for reaction for 70-90 minutes to obtain modified starch.
3. The high-strength corrugated paper according to claim 1, characterized in that: The modified nano material is prepared by mixing titanium dioxide, silicon carbide and boron nitride, adding water and hexadecyltrimethylammonium bromide, and heating for reaction.
4. The high-strength corrugated paper according to claim 3, characterized in that: The weight ratio of titanium dioxide, silicon carbide and boron nitride is 1:(1.2-1.4):(0.5-0.7).
5. The high-strength corrugated paper according to claim 4, characterized in that: The titanium dioxide has a particle size of 10-20 nm and a specific surface area of 30-100 m 2 / g; Silicon carbide particle size 20-60nm, specific surface area: 20-30m 2 / g; Boron nitride particle size 80-140nm, specific surface area 10-20m 2 / g.
6. The high-strength corrugated paper according to claim 5, characterized in that: The preparation method of the modified nanomaterial comprises the following steps: (1) mixing titanium dioxide, silicon carbide and boron nitride to obtain a mixed material; (2) mixing the mixed material and water in a weight ratio of 1:(6-8), adjusting the pH value to 9.5-10 using sodium carbonate, and stirring at 60-65° C. for 3-5 hours to form a suspension; (3) Add hexadecyltrimethylammonium bromide to the suspension, mix and stir evenly, react at 60-65° C. for 4-6 hours, filter, wash to neutrality, and dry to obtain a modified nanomaterial.
7. The high-strength corrugated paper according to claim 6, characterized in that: The added amount of hexadecyltrimethylammonium bromide accounts for 10-15% of the weight percentage of the mixed material.
8. The high-strength corrugated paper according to claim 1, characterized in that: The organosilicon modifier is KH-570 silane coupling agent.
9. The high-strength corrugated paper according to claim 1, characterized in that: The preparation method of the enhancement solution comprises the following steps: (1) mixing modified starch, phenolic resin, modified nanomaterial and water, heating and stirring at 60-70° C. for 45-50 minutes, and cooling to room temperature to obtain an aqueous phase system; (2) mixing epoxy resin, dicyandiamide, dibutyltin dilaurate, organosilicon modifier, aminosilicone oil, epichlorohydrin and acetone, stirring at 50-60° C. for 40-50 min, and cooling to room temperature to obtain an acetone phase system; (3) The aqueous phase system is added to the acetone phase system, and stirred at a rotation speed of 1200-1500 rpm and 50-60° C. for 30-50 min to obtain an enhanced solution.
10. A method for preparing high-strength corrugated paper according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) applying a reinforcing liquid to the surface of a corrugated paper layer and drying the layer to obtain a corrugated paper layer; (2) The rigid corrugated paper layer is adhered to the surface of the face paper and the inner paper by an adhesive to obtain a high-strength new type of corrugated paperboard.
Citation Information
Patent Citations
A new type of high-strength corrugated paperboard and its processing technology
CN117230664B